2010
DOI: 10.1177/0306624x09360662
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment Instruments in Repeat Offending

Abstract: Research in the area of predicting recidivism has produced several well-validated standardized risk assessment instruments. The question arises, which instruments best serve which purposes? The objective of this study was to evaluate and compare several actuarial and dynamic risk assessment instruments as to their predictive accuracy and their usefulness in forensic practice. The sample consisted of 109 violent and sex offenders who had been released from prison in Switzerland between 1994 and 1999, and for wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 16 publications
1
26
0
3
Order By: Relevance
“…Rossegger et al (2011) reported that the interrater reliability of the overall VRAG is strong (ICC = .95), and Douglas, Yeomans, and Boer (2005) reported mean item-level reliability of ICCs ranged from .49 to 1.00, with a mean of .79. Quinsey et al (2006) reported that the predictive validity of the nonviolent CLS scale is within an acceptable range (AUCs = .70-.74).…”
Section: Methodsmentioning
confidence: 99%
“…Rossegger et al (2011) reported that the interrater reliability of the overall VRAG is strong (ICC = .95), and Douglas, Yeomans, and Boer (2005) reported mean item-level reliability of ICCs ranged from .49 to 1.00, with a mean of .79. Quinsey et al (2006) reported that the predictive validity of the nonviolent CLS scale is within an acceptable range (AUCs = .70-.74).…”
Section: Methodsmentioning
confidence: 99%
“…However, only the AUCs for the SIR and STATIC-99 with general recidivism were significantly different from each other. Rossegger et al (2011) compared several tools in a sample of violent and sex offenders released from Swiss prisons. The PCL-R (Hare, 1991) had the highest AUC, followed by the FOTRES (Urbaniok, 2007), the Historical, Clinical, Risk Management-20 (HCR-20;Webster, Douglas, Eaves, & Hart, 1997), the LSI-R, and finally the VRAg, which had the lowest AUC.…”
Section: Use Of the Level Of Service Instruments With Sexual Offendersmentioning
confidence: 99%
“…However, research surrounding its utility for sex offenders is scant. To date, there are few peer-reviewed articles that explore the validity and reliability of LSI-R instrumentation for this group (i.e., Rossegger, Laubacher, Moskvitin, Villmar Palermo, & Endgrass, 2011;Simourd & Malcolm, 1998;Wormith, Hogg, & Guzzo, 2012). Simourd and Malcolm (1998) measured the adequacy of the LSI-R against the Hare Psychopathy Checklist-Revised (PCL-R; Hare, 1991), the General Statistical Information on Recidivism (GSIR; Nuffield, 1982), 3 and the Denial/Minimization Checklist (DMCL; Barbaree, 1991) for a group of federally incarcerated sex offenders (N = 216) in Canada.…”
Section: The Lsi-rmentioning
confidence: 99%